Can Economic Pressure Overcome Social Norms? The Case of Female Labor Force Participation - Ana Rute Cardoso; Louis-Philippe Morin (Institute of Labor Economics (IZA), 2018)
We investigate the potential channels that drive female labor force participation to rise in response to unbalanced sex ratios, in the presence of strong social norms against female employment. One such channel is women's desired labor supply, operating through the marriage market, and the other is employers' demand for female labor. If faced with a reduction in male workforce, do employers turn to women to fill in the gap? Do women enter traditionally male occupations and industries, so that segregation decreases? Does the gender pay gap decline? We exploit exogenous variation in sex ratios across cohorts and regions, by using instruments based on casualties from the Portuguese Colonial War and massive emigration in the 1960s combined with its historical regional patterns. We find that as the sex ratio declined, female participation increased, women entered traditionally male-dominated occupations and industries, and the gender pay gap declined. These findings are consistent with a demand shock. Our estimated impact of sex ratios on marriage market points to a muted supply channel. We complement the quantitative analysis with an archival case. Our findings help to explain an apparent puzzle, a decades-long high female participation in Portugal, as opposed to the other Southern European countries.
Keywords: J21; J23; N34; J22; 330; labor demand; labor force participation; gender segregation; pay gap